2016
DOI: 10.1002/ajh.24347
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of patients with incidental finding of 20q‐ in the bone marrow without a morphologic evidence of myeloid neoplasm

Abstract: Deletion of the long arm of chromosome 20 (20q-) is a frequent finding in bone marrow karyotypes, mainly associated with myeloid neoplasms (MNs). Its clinical significance in the setting of normal bone marrow morphology is unclear. We described the clinical characteristics, cytogenetic findings, and outcome of 102 such patients seen at our institution from 2000-2014. Their median age was 66 years. The indication for bone marrow biopsy was either unexplained cytopenias (48%) or hematologic cancer staging/reeval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is well‐known that a proportion of ICUS patients with abnormal karyotype are at risk of progression to a myeloid malignancy. Jawad et al reported that 15% of the patients with isolated loss of chromosome 20q progressed to a myeloid neoplasm . This phenomenon is also described in healthy elderly individuals with CHIP, where a minor subset develops a hematological cancer .…”
Section: Discussionmentioning
confidence: 90%
“…It is well‐known that a proportion of ICUS patients with abnormal karyotype are at risk of progression to a myeloid malignancy. Jawad et al reported that 15% of the patients with isolated loss of chromosome 20q progressed to a myeloid neoplasm . This phenomenon is also described in healthy elderly individuals with CHIP, where a minor subset develops a hematological cancer .…”
Section: Discussionmentioning
confidence: 90%
“…Based on the presence or absence of cytopenia(s), these patients belong to either a nonneoplastic or preneoplastic category encompassing clonal hematopoiesis of indeterminate potential (CHIP) and clonal cytopenia(s) of undetermined significance 16,17 . The clinical outcome in patients with isolated del(20q) is generally indolent, but 10−25% ultimately develop MDS, MPN, MDS/MPN or AML 6,7,18 . The association of del(20q) with such a wide range of diseases and variable clinical outcomes clearly indicates the underlying genetic and biologic heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the WHO classification (fourth edition) 4 , isolated del(20q) is not considered a definitive evidence for MDS in patients with unexplained cytopenia in the absence of morphologic evidence for MDS 5 , which sometimes results in a diagnostic and therapeutic dilemma. Studies have shown variable clinical outcomes in patients with isolated del(20q) and about 10−25% of patients ultimately evolve into various MNs including AML 6,7 . However, the underlying pathogenic mechanisms associated with MN progression are largely unknown in isolated del(20q) patients.…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of 20q occurs mainly in myeloid malignances, but rarely it is also observed in lymphoproliferative disorders including multiple myeloma [2] . Significant proportion of MM cases with 20q- has been associated with a myeloproliferative diseases and/or dysplastic changes of the hematopoietic tissue and the anomaly in most of these cases was found in the non-plasma cells [4] .…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of the long arm of chromosome 20 is accepted as myeloid cytogenetic marker, because it is a common finding in myelodysplastic syndrome (MDS), acute myeloid leukemia (AML) and Philadelphia negative chronic myeloproliferative neoplasms [1] . Rarely, 20q- is also observed in B-lymphoproliferative diseases, including multiple myeloma (MM) [2] . The role of 20q- in MM especially as a sole anomaly in the karyotype is not fully understood.…”
Section: Introductionmentioning
confidence: 99%